The impact of medical insurance reimbursement on postoperative inflammation reaction in distinct cardiac surgery from a single center - Qin Jiang; Tao Yu; Keli Huang; Xiaobo Huang; Qingfeng Zhang; Shengshou Hu (BMC, 2022)
Abstract Background Evidences shows that socioeconomic status is reversely associated with the risk of morbidity and mortality for people with cardiovascular disease via pro-inflammation mechanism, but the population profile is not deeply defined on. We aimed to investigate the impact of medical insurance coverage on postoperative systemic inflammatory reaction in two kinds of disease populations undergoing distinct cardiac procedures. Methods A total of 515 patients receiving open mitral valve procedure with high-total expense from May 2013 through May 2021 in Sichuan Provincial People's Hospital were retrospectively collected and stratified according to medical insurance reimbursement: low coverage with high out-pocket (< 30%), medium coverage (≤ 60%, but ≥ 30%), and high coverage (> 60%). Another 118 cases undergoing atrium septum defect (ASD) or patent foramen ovale (PFO) occlusion and taking on consistent low-total expense and low-coverage (< 30%) were also classified according to their insured conditions. The postoperative systemic inflammatory response indexes were high sensitivity C-reactive protein (hs-CRP) and the neutrophil-lymphocyte ratio (NLR). Results Low insurance reimbursement population undergoing open mitral valve procedure had a higher level of hs-CRP and NLR but not troponin I protein or lactate within 48 h postoperatively, and higher thoracic drainage, longer ventilation use and stay in intensive care unit. No significant difference in inflammatory indexes existed among diverse medical insurance coverage in population undergoing ASD/PFO occlusion. Conclusions Higher inflammatory reaction and weaker clinical recovery was associated with lower insurance coverage population undergoing open mitral valve procedure but not ASD/PFO interventional occlusion procedure.